Interaksi Sosial Masyarakat Dalam Menjaga Toleransi Antar Umat Beragama Di Kampung Pancasila, Desa Purwoharjo, Banyuwangi : Community Social Interaction in Maintaining Interfaith Tolerance in Pancasila Village, Purwoharjo Village, Banyuwangi - Oktavia Tia Ramadhani (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2024)
This research analyses the social interactions that support interfaith tolerance in Kampung Pancasila, Gumukrejo Hamlet, Purwoharjo Village, Banyuwangi. In the context of Indonesia's multicultural society, Kampung Pancasila serves as a concrete example of how interfaith solidarity and cooperation can be realised through social and religious activities. The research method used is qualitative with a phenomenological approach, which involves in-depth interviews and direct observation of residents, including community leaders. The results show that joint activities, such as community service and interfaith holidays, are important tools in building harmony. However, challenges such as limited access to social assistance and health services, as well as economic inequality, are barriers to active participation. Therefore, efforts are needed from the government and community leaders to increase education on the use of health facilities, strengthen economic assistance programs, and expand interfaith dialogue activities. By implementing these strategies, it is hoped that tolerance and social harmony in Kampung Pancasila can be maintained and developed. This research concludes that inclusive social interactions and active community involvement are crucial to creating a harmonious social life amidst religious diversity.